Influence of HER2-low and HER2-zero status on pathologic complete response and survival in triple-negative breast cancer: a meta-analysis - Qin, Yu; Pu, Chenchen; Fan, Yuping; Zhu, Kepeng (Frontiers in Oncology, 2025)
ObjectiveTo delve into the influence of different status of human epidermal growth factor receptor 2 (HER2) on the long-term survival of patients suffering from triple-negative breast cancer (TNBC), as well as the pathological complete response (pCR) following neoadjuvant therapy (NAT) via meta-analysis.MethodsA computer search in the Embase, PubMed, Web of Science, and Cochrane Library databases was executed up to January 13, 2025, to collect studies related to HER2 status in TNBC patients. The articles were screened per the inclusion and exclusion criteria. The required data were extracted. The study quality was appraised by means of the Newcastle-Ottawa Scale, and statistical analysis was carried out utilizing Stata 15.0 software.Results36 studies involving 54,277 patients with TNBC were included. According to the meta-analysis, the pCR rate after NAT was more notable in the HER2-zero group compared to the HER2-low group (RR = 0.90, 95%CI: 0.86-0.93, P < 0.001). Regarding overall survival (OS), HER2-low patients exhibited a better prognosis (HR = 0.93, 95%CI: 0.90-0.97, P < 0.001). For disease-free survival, breast cancer-specific survival, and recurrence-free survival, HER2-low patients might experience an enhanced prognosis. However, the results did not exhibit statistically significant. The sensitivity analysis confirmed the robustness of the meta-analysis results. No publication bias existed in studies on each outcome indicator.ConclusionHER2 status is essential for the prognostic assessment of TNBC patients, particularly in predicting pCR and OS outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier PROSPERO CRD-420250642369.